PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI PECAHAN DI KELAS IV SD MUJAHIDIN PONTIANAK - Firmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to develop an interactive learning media for fraction material in fourth-grade elementary school, to measure the feasibility level of the learning media, and to assess its readability level by teachers and students. This study employed a Research and Development (R&D) design using the ADDIE model, which includes the stages of Analysis, Design, and Development. The scope of the study was limited to the product development process, expert validation, and limited trials; therefore, it did not extend to the evaluation of learning outcomes. The limited trial was conducted on 15 fourth-grade students of SD Mujahidin Pontianak. The result of this study is an interactive learning media for mathematics instruction. The product feasibility assessment showed a score of 0.92 from material experts, categorized as highly feasible; 1.00 from language experts, categorized as highly feasible; and 1.00 from media experts, also categorized as highly feasible. Furthermore, the readability test results indicated a score of 0.96 from teachers and 0.91 from students, both categorized as very good. Thus, it can be concluded that the interactive learning media developed in this study is feasible to use and has a good level of readability for both teachers and students as an interactive learning medium for fourth-grade mathematics at SD Mujahidin Pontianak.